The Success of The Tourism and Creative Economy Office of The East Jakarta Administrative City in Supervising Health Protocols During The Covid-19 Pandemic in Matraman District - Gagih Pradini; Nova Nur Rizkia; Anisa Putri Kusumaningrum; Fitri Agustiani (CV ODIS, 2022)
The Covid-19 pandemic has made hotels a place that is very vulnerable to virus transmission. The success of the government's policy to regulate and supervise health protocols in the hotel industry so that the transmission of Covid-19 can be prevented is needed. This study, the object of the study was the hotel industry located in the Matraman District, East Jakarta Administrative City. This study assesses the success of the East Jakarta Administrative City Tourism and Creative Economy Office tribes to have a role and responsibility in this supervisory activity. The hotels to be studied are 2 (two) samples and involve several tourists visiting these hotels. The method used is descriptive by triangulation of data interviewing 3 (three) parties to ensure the correctness of the data obtained. Researchers want to know the success of health protocols carried out by the tourism and creative economy offices of the East Jakarta administrative city to the hotel industry during the Covid-19 pandemic in the Matraman sub-district of the administrative city of east Jakarta.